Neolignans - honokiol and 4-O-methylhonokiol - as potential compounds counteracting diabetic complications - current state of knowledge - Katarzyna Małgorzata Szałabska-Rąpała; Weronika Borymska; Ilona Kaczmarczyk-Żebrowska (Polish Pharmaceutical Society, 2022)
Diabetes mellitus is a chronic metabolic disease. It is characterized by hyperglycemia, which means an increased glucose levels in the serum. This disease can be a result of an insufficient insulin production by the pancreatic β cells, lack of tissue response to the action of this hormone or both these states occurring together. In the course of diabetes a disturbed metabolism of carbohydrates, proteins and lipids is observed. These disorders are often accompanied by chronic oxidative stress. Treatment of type 2 diabetes is based on the use of synthetic oral antidiabetic drugs. These drugs provide good glycemic control in the diabetics' body and improve their quality of life, however, they are not without side effects. Therefore, a comprehensive approach to the patient and additional implementation of compounds that allow to reduce the negative effects of oxidative stress and limit the occurrence of diabetic complications in the process of their treatment seem promising. The scientific world is particularly interested in plants with antioxidant properties. Honokiol is a polyphenolic compound from the neolignans group that can be found in the bark of various magnolia species. Both honokiol and 4-O-methylhonokiol are known for their pro-health properties and multidirectional action on the body, including the glycemic control and restoration of proper lipid metabolism. Therefore, this review focuses on arranging the available scientific literature, covering the issues of the influence of neolignans: honokiol and 4-O-methylhonokiol on the health of a patient suffering from type 2 diabetes and its complications. Data collected in this manuscript shows a beneficial effect of these compounds on the organs most exposed to diabetic complications - including the pancreas, heart muscle or kidneys, as well as the prevention of excessive obesity in the context of affecting the white adipose tissue. After an in-depth analysis of many scientific articles, it can be deduced that these compounds may prove to be promising agents supporting conventional therapies with antidiabetic drugs in the treatment of type 2 diabetes and its accompanying diseases.